Evaluation of RCCI engine combustion, performance, and emissions using spirulina micro-algae biodiesel with methane-enriched hydrogen - Munimathan, Arunkumar; Jayabalan, Jaya; Shanmugam, Manoj Kumar; Majdi, Hasan Sh; Asif, Mohammad; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The creation of the internal combustion engine played a crucial role in the growth of the modern world to its current condition, which occurred at a faster speed than it had been previously. One of the numerous offshoots of a reciprocating engine is the source of inspiration for nearly every aspect of the modern society that we live in today. The relevance and necessity of engines, particularly in the transportation industry, have largely hidden the negative effects that engines have on the environment as a result of their emissions. This is especially true of the emissions that engines produce. A number of major issues have arisen as a consequence of this negligent application, including the release of greenhouse gases into the environment, the creation of situations that are hazardous to human health, and the depletion of fossil resources. Using methane-enriched hydrogen and spirulina microalgae biodiesel as low and high-reactive fuels, respectively, the objective of this work is to ascertain the characteristics of an RCCI engine that utilizes these fuels. Dimethyl ether, diesel, and microalgae spirulina biodiesel are combined in the following proportions in order to make eighty percent of the hydrogen refueling fuel (HRF): Dimethyl ether, diesel, and biodiesel make up 48% of the total. Variations will be made to the settings of the engine in order to explore the effects of using methane-enriched hydrogen as twenty percent of the lowreactive fuel. This fuel blend will be used. Methane to hydrogen ratios in the low reactive fuel blend can range anywhere from 1% to 5%, with concentrations of 1%, 2%, 3%, 4%, and 5% accordingly. The ratio can also be anywhere in between. The characteristics study is carried out by adjusting the speed at which the brakes are applied and the pressure at which the fuel is injected into the engine, all while maintaining the compression ratio at 17.5:1. The characteristics of the emissions of NOx, CO2, smoke, and hydrocarbon, as well as the features of the performances of BTE, BSFC, and EGT, are all included in this classification. The findings of the experiments indicate that the utilization of fuel mixtures has the potential to reduce the amount of emissions produced by engines while simultaneously enhancing the performance of the engines.
Keywords: Low reactive fuel; Engine performance; High reactive fuel; Biodiesel; Emission control; DIESEL-ENGINE; GENERATION; Chemistry; Electrochemistry; Energy & Fuels